2017
DOI: 10.4236/mrc.2017.64010
|View full text |Cite
|
Sign up to set email alerts
|

γ-Alumina-Supported Ni-Mo Carbides as Promising Catalysts for CO<sub>2</sub> Methanation

Abstract: CO 2 methanation with Hydrogen to form CH 4 offers a solution for off-peak renewable energy storage. γ-alumina-supported Mo and Ni-Mo catalysts were used in CO 2 methanation, either in their reduced or in their carburized form. The presence of Ni improved the carburization extent of Mo-species, resulting in increased catalytic activity and selectivity for the catalytic CO 2 methanation reaction. Carburization generally enhances the basicity of the materials and thus CO 2 absorption on their surface. At 300˚C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The fitted curves of the doublet 3d 3/2 and 3d 5/2 are indicated by the red and green lines, respectively, in Figure 4B,C. Coherently, the binding energy values of Mo ions in the 4 + and 6 + oxidation states in the samples are in good agreement with the literature data 54,59,60 . Lastly, Figure 4C shows the main doublet of S 2p located at binding energies of 161 and 163 eV are ascribed to the S 2p 3/2 and S 2p 1/2 , respectively 60‐62 …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The fitted curves of the doublet 3d 3/2 and 3d 5/2 are indicated by the red and green lines, respectively, in Figure 4B,C. Coherently, the binding energy values of Mo ions in the 4 + and 6 + oxidation states in the samples are in good agreement with the literature data 54,59,60 . Lastly, Figure 4C shows the main doublet of S 2p located at binding energies of 161 and 163 eV are ascribed to the S 2p 3/2 and S 2p 1/2 , respectively 60‐62 …”
Section: Resultssupporting
confidence: 80%
“…The peak centered in the range of 855 to 860 eV is attributed to Ni 2p 3/2 and the peak centered in the range of 873 to 878 eV is ascribed to Ni 2p 1/2, which are corresponding to characteristic features of metallic Ni. The other two peaks centered at around 860 and 880 eV are considered as shake up type peaks of Ni 53‐56 . As seen in Figure 4A‐C, all the four characteristic peaks of metallic Ni are fitted well.…”
Section: Resultsmentioning
confidence: 79%
“…Previous research showed that an alumina supported NiMo catalyst could be used to convert vegetable oil to alkanes and alkylbenzene [ 79 ]. In addition to that, alumina supported NiMo and CoMo catalysts are applicable as an effective deoxygenation catalyst to produce hydrocarbon products [ 80 ]. Nevertheless, the metal-based catalyst also resulted in the decrement of yield due to coke formation and high acidity.…”
Section: Catalysis In Catalytic Pyrolysis Of Triglyceride Feedstocksmentioning
confidence: 99%
“…Hence there is clear connection between the carbide structure and the enhanced CO2-methanation performance is deemed to be ascribed to the carburization process. Generally, carburisation enhances the basicity of the resulting Ni-Mo2C/Al2O3 catalyst and thus CO2 absorption/activation on its surface is favoured [70].…”
Section: Molybdenum Carbidementioning
confidence: 99%